Análise do Perfil de Utilização da Terapêutica Empírica Antibiótica Instituída em Infeções do Trato Urinário Adquiridas na Comunidade (ITU-AC) - João Pedro Aguiar; Patrícia Cavaco Silva; Filipa Alves da Costa (Formifarma, LDA., 2014)
Objective: To characterize the pattern of utilization of antibiotic regimens for Community-Acquired Urinary Tract Infection (CA-UTI). Study Design: Prospective Longitudinal Study. Place: Community pharmacies from the counties of Almada, Amadora, Cascais, Lisboa, Oeiras and Sintra. Population: Patients with CA-UTI who resorted to participating pharmacies. Methods: In the initial phase patients completed a questionnaire for sociodemographic characterization of the sample and to collect information about the therapeutic and recurrence of UTI. After finalizing therapy, patients answered a telephone interview in order to characterize the usage profile (according to the modified scale of 4 items MMAS). The results were processed using the program IBM SPSS version 20.0. Results: A sample of 33 patients was obtained, but we were only able to characterize the usage profile of 21 of them. Given the therapy indicated, most of the patients used Fosfomycin (47.6%, n = 10), followed by Nitrofurantoin (23.8%, n = 5), both first-line therapy. For the usage profile, it was found that 81% (n = 17) patients were classified as compliant. Among the non-adherent, half were classified as unintentional and half as intentional. Conclusions: In this study, it was found that most patients were adherent to the antibiotic therapy and only a small proportion was classified as non-compliant. In terms of conclusion, it was found that the value found for non-adherence (19%) is consistent with the values reported in literature (22%).